Assessing the impact of adopting a competency-based medical education framework and ACGME-I accreditation on educational outcomes in a family medicine residency program in Abu Dhabi Emirate, United Arab Emirates - Baynouna AlKetbi, Latifa; Nagelkerke, Nico; AlZarouni, Amal A.; AlKuwaiti, Mariam M.; AlDhaheri, Ruwaya; AlNeyadi, Amna M.; AlAlawi, Shamma S.; AlKuwaiti, Mouza H. (Frontiers in Medicine, 2024)
Competency-Based Medical Education (CBME) is now mandated by many graduate and undergraduate accreditation standards. Evaluating CBME is essential for quantifying its impact, finding supporting evidence for the efforts invested in accreditation processes, and determining future steps. The Ambulatory Healthcare Services (AHS) family medicine residency program has been accredited by the Accreditation Council of Graduate Medical Education-International (ACGME-I) since 2013. This study aims to report the Abu Dhabi program's experience in implementing CBME and accreditation.1. Compare the two residents' cohorts' performance pre-and post-ACGME-I accreditation.2. Study the bi-annually reported milestones as a graduating residents' performance prognostic tool.All residents in the program from 2008 to 2019 were included. They are called Cohort One-the intake from 2008 to 2012, before the ACGME accreditation, and Cohort Two-the intake from 2013 to 2019, after the ACGME accreditation, with the milestones used. The mandatory annual in-training exam was used as an indication of the change in competency between the two cohorts. Among cohort two ACGME-I, the biannual milestones data were studied to find the correlation between residents' early and graduating milestones.A total of 112 residents were included: 36 in cohort one and 76 in cohort two. In cohort one, before the ACGME accreditation, no significant associations were identified between residents' graduation intraining exam and their early performance indicators, while in cohort two, there were significant correlations between almost all performance metrics. Early milestones are correlated with the graduation in-training exam score. Linear regression confirmed this relationship after controlling the residents' undergraduate Grade Point Average (GPA). Competency development continues to improve even after residents complete training at Post Graduate Year, PGY4, as residents' achievement in PGY5 continues to improve.Improved achievement of residents after the introduction of the ACGME-I accreditation is evident. Additionally, the correlation between the graduation in-training exam and graduation milestones, with earlier milestones, suggests a possible use of early milestones in predicting outcomes.